Neural mechanisms of intermodal sustained selective attention with concurrently presented auditory and visual stimuli - Saupe, Katja; Schröger, Erich; Andersen, Søen K.; Müller, Matthias M. (Frontiers in Human Neuroscience, 2009)
We investigated intermodal attention effects on the auditory steady-state response (ASSR) and the steady-state visual evoked potential (SSVEP). For this purpose, 40 Hz amplitude modulated tones and a stream of flickering (7.5 Hz) random letters were presented concurrently. By means of an auditory or visual target detection task, participants’ attention was directed to the respective modality for several seconds. Attention to the auditory stream led to a significant enhancement of the ASSR compared to when the visual stream was attended. This attentional modulation was located mainly in the right superior temporal gyrus. Vice versa, attention to the visual stream especially increased the second harmonic response of the SSVEP. This modulation was focused in the inferior occipital and lateral occipitotemporal gyrus of both hemispheres. To the best of our knowledge, this is the first demonstration of amplitude modulation of the ASSR and the SSVEP by intermodal sustained attention. Our results open a new avenue of research to understand the basic neural mechanisms of intermodal attention in the human brain.